2008
DOI: 10.4103/0378-6323.38431
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study of cutaneous drug eruptions in 200 patients

Abstract: Two hundred patients (112 males and 88 females) with cutaneous drug eruption were studied. The aim was to recognize the offending drug, to evaluate mortality and morbidity, educate the patient and avoid self-administration and readministration of drugs. Fixed drug eruption was the commonest reaction, seen in 61 patients; other reactions being urticaria and angioedema,morbilliform rash in 37, pruritus in 25, Stevens Johnson Syndrome (SJS) in 6, purpura in 6, exfoliative dermatitis in 5,photosensitivity in 5, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
51
3
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 0 publications
10
51
3
1
Order By: Relevance
“…This was in cofirmity with Sharma VK et al, however Marfatia et al reported fixed drug eruption to be the most common pattern followed by urticaria, morbilliform rash and pruritus. 5,7 Similar observation was also made by Pudukadan et al where fixed drug eruption was the most common presentation (31.1%) followed by maculopapular rash, SJS-TEN and urticaria (Table 2). 6 Antimicrobial group of drugs were found to be the most common culprit (29.33%) in our study as opposed to Marfatia et al where NSAIDS formed the major group (21%).…”
Section: 6supporting
confidence: 67%
“…This was in cofirmity with Sharma VK et al, however Marfatia et al reported fixed drug eruption to be the most common pattern followed by urticaria, morbilliform rash and pruritus. 5,7 Similar observation was also made by Pudukadan et al where fixed drug eruption was the most common presentation (31.1%) followed by maculopapular rash, SJS-TEN and urticaria (Table 2). 6 Antimicrobial group of drugs were found to be the most common culprit (29.33%) in our study as opposed to Marfatia et al where NSAIDS formed the major group (21%).…”
Section: 6supporting
confidence: 67%
“…Previous studies also suggest FDE as the most common type of cutaneous ADRs. 3,14,15 The most commonly incriminated drugs in our study are NSAIDs (41.66%), anti-microbials (25%), anti-convulsants (25%), anti-diarrhoeal (3.33%), anti-neoplastic (3.33%), corticosteroids (3.33%) and herbal medicine (3.33%). In the present study, herbal medicine caused 1.66% of cutaneous ADRs which included SJS (one case).…”
Section: 12-15mentioning
confidence: 99%
“…A community study in India also showed that NSAID is the major cause for SJS/ TEN and exanthema in drug allergy. 9 Moreover, Noguera-Morel et al 10 also showed a similiar result in their study of pediatric drug allergy.…”
Section: Discussionmentioning
confidence: 91%
“…Several studies have discovered that antibiotic and antiinflammatory is the major causative agent in drug allergy. 3,8,9 Another study in Malang, Indonesia, also showed that paracetamol and penicillin are the major suspected causative drugs for drug allergy in pediatrics. 4 The majority of the suspected causative drugs generates the drug allergy when it is given as a single drug, and not combined with the other drug, except for anti-tuberculosis drugs which is always given as a combination of several different antibiotics.…”
Section: Discussionmentioning
confidence: 99%